Learning Strategies in Increasing the Interest in Memorizing Al- Qur'an Hafidzpreneur Students at Tazkia Institute Bogor - Inda, Inda; Heryahya, Andang (Universitas Tanjungpura, 2024)
Tazkia Institute has been implementing the tahfidz program since 2017 until now. This program applies various learning strategies for memorizing the Qur'an to achieve the goals of the tahfidz program. The study aims to find out how learning strategies in increasing the interest in memorizing hafidzpreneur students are applied at Tazkia Bogor Institute. The method used by the author is with a qualitative descriptive approach. Data collected through observation, interviews, and documentation. This research is motivated by several factors so that student interest in memorizing the Qur'an decreases. Therefore, it is necessary to have a strategy for coaches in increasing students' interest in memorizing in order to complete the tahfidz and academic programs within four years. The results of this study indicate that the learning strategy in increasing interest in memorizing the Qur'an consists of: First, the planning stage in the form of curriculum preparation or tahfidz learning time system, Qur'an Camp activities, and memorization certification models. Second: the implementation of learning consists of initial activities opened with greetings and prayers to start tahfidz classes to core activities with memorization deposits to musyrifah until closing activities. Third: factors that influence students' interest in memorizing, fourth: efforts made by ustadz ustadzah by taking several approaches such as personal approach, general approach, and sharing sessions with students in order to encourage enthusiasm in memorizing.